THE SYNTHESIS AND DEVELOPMENT OF THE MANAGEMENT SYSTEM WITH THE MAIN STOCK - Aleksandr N. Garmash; Vadim A. Bolshakov; Mikhail S. Gasparian (Статистика и экономика, 2016)
In the present paper is an extension of the paper «Some generalizations of the management system with the main stock» published in [1]. The analytical dependence of the random variable rate of working capital for the most common of the probability distribution in the management of stocks. The calculation of the probability of a shortage in the unit needs. The possibility of using the results of research in the ERP-systems.